Does audit improve diabetes care in a primary care setting? A management tool to address health system gaps - Pruthu, T. K. (J Nat Sci Biol Med, 2015)
INTRODUCTION: Diabetes mellitus is one of the emerging epidemics. Regular clinical and biochemical monitoring of patients, adherence to treatment and counseling are cornerstones for prevention of complications. Clinical audits as a process of improving quality of patient care and outcomes by reviewing care against specific criteria and then reviewing the change can help in optimizing care. OBJECTIVE: We aimed to audit the process of diabetes care using patient records and also to assess the effect of audit on process of care indicators among patients availing diabetes care from a rural health and training center in Puducherry, South India. MATERIALS AND METHODS: A record based study was conducted to audit diabetes care among patients attending noncommunicable disease clinic in a rural health center of South India. Monitoring of blood pressure (BP), blood glucose, lipid profile and renal function test were considered for auditing in accordance with standard guidelines. Clinical audit cycle (CAC), a simple management tool was applied and re-audit was done after 1-year. RESULTS: We reviewed 156 and 180 patients records during year-1 and year-2, respectively. In the audit year-1, out of 156 patients, 78 (50%), 70 (44.9%), 49 (31.4%) and 19 (12.2%) had got their BP, blood glucose, lipid profile and renal function tests done. Monitoring of blood glucose, BP, lipid profile and renal function improved significantly by 35%, 20.7%, 36.4% and 56.1% over 1-year. CONCLUSION: CAC improves process of diabetes care in a primary care setting with existing resources.